Website-Based TIQ Application for Mangrove Tourism Entrance Tickets for Pari City Village - Isnar Sumartono; Ahmad Akbar; Tway Wandiky Lumban Gaol (Yayasan Sinergi Multidimensi Kreatif, 2024)
This research aims to develop an entrance ticket application based on QR Code